aoDouble Timea Surgical Technique for Treatment of Pilonidalis Cyst: First Results (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: pilonidal cyst; surgical treatment of pilonidal cyst; sinus pilonidalis